2021
DOI: 10.1038/s41598-021-84975-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of the spinal instability neoplastic score (SINS) for predicting vertebral compression fractures after radiotherapy in spinal metastases: a meta-analysis

Abstract: Radiotherapy has played an important role in the treatment of spinal metastases. One of the major complications of radiotherapy is vertebral compression fracture (VCF). Although the spinal instability neoplastic score (SINS) was developed for evaluating spinal instability in patients with spinal metastases, it is also commonly used to predict VCF after radiotherapy in patients with spinal metastases. However, its accuracy for predicting radiotherapy-induced VCF and precision remain controversial. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, the SINS overall score was not predictive of PVF risk, which was also reported by Germano et al (2016). A recent meta-analysis (Kim et al, 2021) suggested that higher SINS scores moderately predict PVF in patients after radiotherapy with a pooled sensitivity of 0.790 (95% CI 0.723-0.843) and a pooled specificity of 0.546 (0.462-0.62). Given the significant challenges of quantifying the risk of PVF clinically (Fourney et al, 2011;Boehling et al, 2012), better fracture risk prediction represents an important and unmet medical need (Galasko, 1986;Aebi, 2003;Bartanusz and Porchet, 2003;Groot et al, 2006).…”
Section: Introductionmentioning
confidence: 57%
“…However, the SINS overall score was not predictive of PVF risk, which was also reported by Germano et al (2016). A recent meta-analysis (Kim et al, 2021) suggested that higher SINS scores moderately predict PVF in patients after radiotherapy with a pooled sensitivity of 0.790 (95% CI 0.723-0.843) and a pooled specificity of 0.546 (0.462-0.62). Given the significant challenges of quantifying the risk of PVF clinically (Fourney et al, 2011;Boehling et al, 2012), better fracture risk prediction represents an important and unmet medical need (Galasko, 1986;Aebi, 2003;Bartanusz and Porchet, 2003;Groot et al, 2006).…”
Section: Introductionmentioning
confidence: 57%
“…Although conventional RT is most commonly utilized for spinal SREs, the occurrence of new VBC during RT has not been fully investigated previously (10,11,(15)(16)(17)(18)(19)(20)(21)(22)(23). Shi (10).…”
Section: Discussionmentioning
confidence: 99%
“…These ndings align with existing literature (that underscores the signi cance of early detection and surgical intervention in enhancing the outcomes of patients with spinal metastases. [3][4][5][6]12,14,16,19,[24][25][26][27] Furthermore, our study highlights the relevance of the Spinal Instability Neoplastic Score (SINS) as a valuable tool for informing treatment decisions. By employing SINS to assess the degree of instability and the necessity for surgery, healthcare providers can customize treatment plans to individual patients, potentially augmenting their HRQoL and survival.…”
Section: Survival Ratesmentioning
confidence: 99%
“…Key features of metastasis of the vertebral column include pain, neurological de cits that can cumulate in a para-or tetraplegia, and biomechanical instability. The latter was addressed by development of the Spinal Instability Neoplastic Score (SINS) [2][3][4][5][6][7][8][9][10][11][12][13][14] . This scoring system takes several factors such as the location, pain, and type of spinal lesion into account to determine the degree of instability and the need for surgical intervention.…”
Section: Introductionmentioning
confidence: 99%